2015
DOI: 10.1111/tpj.12877
|View full text |Cite
|
Sign up to set email alerts
|

Roles and activities of chromatin remodeling ATPases in plants

Abstract: These authors contributed equally to this paper. SUMMARYChromatin remodeling ATPases and their associated complexes can alter the accessibility of the genome in the context of chromatin by using energy derived from the hydrolysis of ATP to change the positioning, occupancy and composition of nucleosomes. In animals and plants, these remodelers have been implicated in diverse processes ranging from stem cell maintenance and differentiation to developmental phase transitions and stress responses. Detailed invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 191 publications
(358 reference statements)
3
134
0
1
Order By: Relevance
“…Emerging evidence has revealed that epigenetic, chromatin-based regulation, including DNA methylation, histone modification, nucleosome remodeling and regulation by non-coding RNAs, plays a central role in self-renewal, differentiation and reprogramming in both the animal and plant kingdoms (Fisher and Fisher, 2011;Han et al, 2015;Ikeuchi et al, 2015;Orkin and Hochedlinger, 2011). A number of epigenetic regulators have been implicated in the myogenic lineage program.…”
Section: Epigenetic Regulation Of Stomatal Developmentmentioning
confidence: 99%
“…Emerging evidence has revealed that epigenetic, chromatin-based regulation, including DNA methylation, histone modification, nucleosome remodeling and regulation by non-coding RNAs, plays a central role in self-renewal, differentiation and reprogramming in both the animal and plant kingdoms (Fisher and Fisher, 2011;Han et al, 2015;Ikeuchi et al, 2015;Orkin and Hochedlinger, 2011). A number of epigenetic regulators have been implicated in the myogenic lineage program.…”
Section: Epigenetic Regulation Of Stomatal Developmentmentioning
confidence: 99%
“…It has the canonical domains found in this family of proteins (Farrona et al, 2004, Han et al, 2015. BRM protein includes a N-terminal region with a glutamine-rich domain and a helicase SANT-associated domain (HSA).…”
Section: Brm the Core Atpase Of Swi/snf Crc Structure Of Brm Proteinmentioning
confidence: 99%
“…The SnAC domain is known to be required for mobilizing nucleosomes and its presence is required in vivo for transcription regulation but not for the complex organization, the substrate recognition or the recruitment function (Sen et al, 2013, Sen et al, 2011. BRM has a C-terminal domain that contains an AT-hook and a bromodomain (Farrona et al, 2007, Sen et al, 2011, Han et al, 2015. The AT-hook and the bromodomain are important domains for the BRM association with chromatin.…”
Section: Brm the Core Atpase Of Swi/snf Crc Structure Of Brm Proteinmentioning
confidence: 99%
See 2 more Smart Citations